Ataxia telangiectasia: presentation and diagnostic delay. Issue 4 (31st October 2016) - Devaney, Rebecca; Pasalodos, Sara; Suri, Mohnish; Bush, Andy; Bhatt, Jayesh M
Abstract : Background and aims: Ataxia telangiectasia (A-T) is a rare progressive, multisystem genetic disease. Families of children with ultra-rare diseases often experience significant diagnostic delays. We reviewed the diagnostic process for A-T in order to identify causes of delay in an attempt to facilitate earlier identification of A-T in the future. Methods: A retrospective case note review of 79 children at the National Paediatric A-T clinic seen since May 2009. Data were collected on the nature and age of initial symptoms, the age at first presentation, measurement of alpha feto-protein (AFP) and age of genetic diagnostic confirmation. Results: At presentation, 71 children (90%) had ataxia. The median presentation delay (from first parental concern to presentation) was 8 months (range 0–118 months), and the median diagnostic delay (genetic confirmation of diagnosis) was 12 months (range 1–109 months). Conclusions: There are significant delays in presentation and diagnostic confirmation of A-T. A greater awareness of A-T and early measurement of AFP may help to improve this.